“Version 1.4.0 – pyfao56: FAO-56 evapotranspiration in Python” - Kelly R. Thorp; Dinesh Gulati; Meetpal Kukal; Reagan Ames; Tyler Pokoski; Kendall C. DeJonge (SoftwareX)
The pyfao56 software package is a Python-based implementation of the standardized evapotranspiration (ET) methodologies described in Irrigation and Drainage paper No 56 of the Food and Agriculture Organization of the United Nations, commonly known as FAO-56. This update improved pyfao56 by 1) updating ET variables and terminology, 2) adding ET calculations using the FAO-56 single crop coefficient approach, 3) including data on crop coefficients, growth stage lengths, and rooting depths as published in FAO-56 tables, and 4) incorporating optional crop coefficient adjustments for mid-season and late-season weather conditions when mean values for minimum relative humidity and wind speed deviate from 45 % and 2 m s-1, respectively. Other minor edits included the addition of the Kling-Gupta efficiency as a goodness-of-fit statistic, error handling when the provided soil profile depth is shallower than the maximum rooting depth, and improved management of the model version number in the source code.